China's stock market - Li, Ting (KDI School, 1999)
This thesis provides a comprehensive overview and some economic analyses of the development and prospects of China’s stock market. The significant progress that China’s stock market has achieved has been widely recognized around the world. Based on a basic framework of China’s economic reforms and stock market development, the thesis attempts to discuss several major bottleneck issues that impeded the development of China’s stock market. It is my personal hope that this thesis will contribute to some extent to the vast literature on China’s stock market with its most up-to-date information within a systematic framework. China is experiencing rapid changes in all aspects of its stock market, and almost all the research on this sector needed most updated data to support. However, most of the research so far is limited to a historical overview of China’s stock market, very few are recent enough to address the issues facing China’s stock market, such as, state shares and legal person shares, A shares and B shares, as well as the stock market under the WTO accession. This thesis will be helpful to those people who are interested in studying China’s stock market
Thesis(Master) --KDI School:Master of Economics and Public Policy,1999